In-depth characterization of ubiquitin turnover in mammalian cells by fluorescence tracking. Issue 8 (19th August 2021) - Kudriaeva, Anna A.; Livneh, Ido; Baranov, Mikhail S.; Ziganshin, Rustam H.; Tupikin, Alexey E.; Zaitseva, Snizhana O.; Kabilov, Marsel R.; Ciechanover, Aaron; Belogurov, Alexey A.
Summary: Despite almost 40 years having passed from the initial discovery of ubiquitin (Ub), fundamental questions related to its intracellular metabolism are still enigmatic. Here we utilized fluorescent tracking for monitoring ubiquitin turnover in mammalian cells, resulting in obtaining qualitatively new data. In the present study we report (1) short Ub half-life estimated as 4 h; (2) for a median of six Ub molecules per substrate as a dynamic equilibrium between Ub ligases and deubiquitinated enzymes (DUBs); (3) loss on average of one Ub molecule per four acts of engagement of polyubiquitinated substrate by the proteasome; (4) direct correlation between incorporation of Ub into the distinct type of chains and Ub half-life; and (5) critical influence of the single lysine residue K27 on the stability of the whole Ub molecule. Concluding, our data provide a comprehensive understanding of ubiquitin-proteasome system dynamics on the previously unreachable state of the art. Graphical abstract: Highlights: Ub half-life in mammalian cells is 4 h On average six Ub molecules are conjugated with a substrate One Ub moiety is lost per four episodes of engagement of substrate by proteasome Single lysine residue K27 is critical for the stability of the whole Ub molecule Abstract : Kudriaeva et al. determined several fundamental characteristics of ubiquitin metabolism in mammalian cells, including its half-life and turnover, average number of ubiquitins per substrate as a dynamic equilibrium between ubiquitin ligases and deubiquitinated enzymes, stability of differentially linked polyubiquitin chains and how often ubiquitin dies when it meets proteasome.